Smart Buildings menggunakan Hyperledger Fabric Blockchain untuk Manajemen Transaksi dan Pemodelan 3D - Asmiatun, Siti; Novita Putri, Astrid; Zaman, Badroe (Jurnal Teknologi Terpadu, 2023)
Home construction or home renovation must consider many complex factors. That is because there will be errors / human errors that occur. The impact of that will cause losses to architectural services and eliminate dissatisfied customer trust. Another problem is that customers use intermediaries or third parties in the home construction/renovation process, increasing funds. That is because the process of building/renovating the house is different fromations. This research utilizes a hyper ledger fabric blockchain and intelligent building technology to manage architect and consumer management without intermediaries. Technology can manage home construction/renovation through information on 3-dimensional house plans, initial home budgets, prices for building materials, and daily material needs. The purpose is to monitor the building/renovation of a house without a third party. This study uses the Multimedia Development Life Cycle (MDLC) Development Method to make its application. Meanwhile, blockchain technology is applied using Hyperledger Fabric Software. This research can increase trust and benefit both the customer and the developer. The results of this study are that by making block numbers 65 – 66, it is recorded that each transaction has a processing time from 2022-08-14 02:32:47 to 2022-08-14 02:32:50; it takes approximately.